INDIAN S- 400 MISSILE DILEMMA (International Conference on Social and Islamic Studies, 2021)
ince the partition, India's hegemonic posture in South Asian region turned the region into a very complex and dramatic situation. The Indian aspiration to accumulate more hegemonic superiority consequences a tit for tat arms procurement race. This sort of race for arms andnuclear power has historically engineered four wars within India and Pakistan, a long-lastingenmity and hatred impacting the ultimate region. On the other hand, the border clashes and recent border standoffs of India and China are scenarios of the region. In such circumstances, India's quest for attaining and procuring S-400 missile is a clear depiction of geopolitical significance. Moreover, this procurement is a geopolitical movement of different dimensions and dynamics of the region complexities. Certain deal creates an arms race within the region in the context of offensive and defensive realism which predicts the region in security dilemma. This deal not only challenges the hegemonic role of US in the region but also analyzes the hypocrisy of US if India fails to get sanctioned.